ANALYTIC SOLUTION OF NONLINEAR LEYBENSON EQUATION IN THE THEORY OF FILTRATION - B. V. Аlexeev (Тонкие химические технологии, 2016)
Analytic solution of nonlinear Leybenson equation in the theory of filtration is obtained. Analytical solutions of the partial differential equations are presented in the explicit algebraic form. The integral surfaces in three dimensions are presented.